Smart government at the regional secretariat organization section of Sumedang district - Shinta Puspitasari; Rizky Ilhami (Jurnal Scientia, 2024)
Sumedang Regency is one of the districts in West Java Province that has implemented the Smart Government concept to increase the effectiveness of its government role. In 2020 Sumedang Regency succeeded in winning the Innovative Government Award (IGA) with an Electronic Based Government System (SPBE) index of 3.81. This success is reflected in the Regional Secretariat of Sumedang Regency which has implemented Smart Government, especially in the Regional Secretariat Organization Section. This research aims to find out what and how Smart Government is implemented in the Regional Secretariat of the Sumedang Regency Organization Section in a more comprehensive manner. This research uses descriptive research methods with a qualitative approach. The data collection techniques are carried out through direct observation, interviews with predetermined informants, and accompanying documentation. This technique is carried out so that the required data can be obtained more concretely. The results of the research show that the Regional Secretariat Organization Section of Sumedang Regency has been able to implement Smart Government, but the human resources and infrastructure it has are not yet capable of optimizing the implementation of Smart Government. This is the impact of employee mutations caused by changes in structural positions to functional ones. This problem is further strengthened by findings in the field that human resources with the required competencies and expertise have not been able to optimize their roles and functions in implementing Smart Government in Sumedang Regency.